Formulasi dan Uji Aktivitas Sediaan Krim Antioksidan Ekstrak Daging Buah Rumbiah (Metroxylon Sagu Rottb) - Julia Megawati Djamal; Fivianti Fivianti; I Made Rantiasa; Febrianika Ayu Kusumaningtyas (Universitas Muhamadiyah Manado, 2026)
Rumbia fruit contains various bioactive secondary metabolites, particularly flavonoids, which are recognized for their antioxidant properties. These compounds contribute to the prevention of oxidative damage by scavenging and neutralizing free radicals. To enhance its practicality and ease of application, the fruit pulp extract was incorporated into a cream formulation. This study aimed to develop a topical cream containing rumbia fruit pulp extract and to evaluate its physicochemical characteristics. The antioxidant activity of the formulated cream was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. The results demonstrated that the extract could be successfully formulated into a stable cream preparation. Furthermore, the formulated cream complied with the quality requirements for topical creams, as evidenced by satisfactory organoleptic properties, homogeneity, pH value, spreadability, and adhesiveness. Antioxidant evaluation revealed a color transition from purple to yellow during the DPPH assay, indicating the ability of the extract to scavenge free radicals and exhibit antioxidant activity.